DAMPAK TINGKAT LITERASI KEUANGAN, FOMO, DAN OVERCONFIDENCE TERHADAP PENGAMBILAN KEPUTUSAN INVESTASI MAHASISWA UIN MALANG - Mochamad Riski Fajar Kurniawan; Maretha Ika Prajawati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The main objective of this study is to examine how 2022 management students at the Faculty of Economics, UIN Maulana Malik Ibrahim Malang, make investment decisions related to financial literacy, overconfidence, and FOMO. Purposive sampling was used to select 72 respondents for this quantitative study. Data were collected through Google Forms, and IBMiSPSS Statistics 23 wasiused as the analysis tool for the multiple linear regression method. The findings indicate that although FOMO has an insignificant positive impact on investmentidecisions, financial literacy and overconfidence have a significantipositive impact on investmentidecisions. These results highlight the importance of understanding financial literacy and managing psychological biases when making investment decisions.